Assessment of the return on equity of an enterprise using the dupont method: Abstract, Introduction, Literature Review, Methodology, Results and discussions, Conclusion, References. - Kishibayeva, B. S.; Jaxybekova, G. N. (Journal of Economic Research & Business Administration, 2023)
The article discusses the principle of asset profitability analysis based on the DuPont model. The profitability of equity was described on the basis of three basic formulas for calculating the model and used in the analysis. The subject of the study is the development of the enterprise of JSC "Caspian Oil" for 2019-2021. The purpose of the study is to evaluate the effectiveness and factor analysis of the company. To achieve this goal and objectives, formulas for calculating indicators and the Dupont method were used. The analysis of return on equity on the example of JSC "Caspian Oil" using the DuPont three-factor model and the analysis based on the indicator of the open annual report 2019-2021. The change in net return on assets was revealed due to three factors, namely an increase in net profit, a slowdown in asset turnover and a deterioration in the capital structure. As a result of the work, it turned out that one of the most important and meaningful coefficients is ROE (return on equity). It shows the effectiveness of the use of shareholders’ funds and the company in question is a joint-stock company. Using a factor analysis of the profitability of an oil and gas company, the authors showed that the growth of net profit, equity and profitability are more sensitive to changes in net profit by the same percentage. Keywords: profitability, efficiency of company, Dupont model, factor analysis of ROE, net profit, equity, financial analysis